Seismic Retrofitting Solutions for Precast RC Industrial Buildings Struck by the 2012 Earthquakes in Northern Italy - Minghini, Fabio; Tullini, Nerio (Frontiers in Built Environment, 2021)
In 2012, the North of Italy was hit by a seismic sequence characterized by two main events occurred on May 20 and 29 with MW = 6.1 and 6.0, respectively. Those earthquakes were particularly severe toward precast Reinforced Concrete (RC) structures not designed for seismic resistance. In the past years, the authors implemented a database collecting damage data and typological information on the industrial buildings struck by the Emilia earthquakes. That database was used to develop empirical fragility curves, which highlighted the considerable vulnerability of precast buildings conceived in accordance with pre-seismic code provisions. More recently, the interventions of seismic retrofitting on the same buildings, funded by the Emilia-Romagna region and designed by engineers which were directly hired by the companies, were examined in detail and critically revisited. A selection of these interventions is presented in this paper, which analyzes the effectiveness of the various retrofitting solutions, with a specific attention to the force transfer mechanisms between existing structures and strengthening systems. The interventions are divided between column strengthening (based, for example, on RC or steel jacketing) and interventions aimed at providing the building with a suitable earthquake resistant system (based, for example, on either the use of the existing cladding panels or the implementation of new bracing systems). Graphical representations of the analyzed solutions with the relevant construction details are provided.